Exploring micronutrient deficiency risks in Africa using projections of the food system - Gabriel, Sherwin; Sulser, Timothy B. (Global Trade Analysis Project, 2022)
Micronutrient deficiencies (MND) remain an important challenge in the 21st century, complicated by climate, economic, and demographic change. However, the lack of recent and reliable survey data challenge understanding of the magnitude and risks posed by MNDs. We examine projections of food availability to 2050, for 49 African countries, under various climate and socio-economic futures, using a global, multi-market partial equilibrium model. Food availability is used to estimate micronutrient availability, accounting for edible portions, nutrient loss, and country-specific characteristics of consumed foods. Projections from an ensemble of sixty scenarios are analysed and assessed against recommended daily intake to gauge nutrient adequacy. Of the panel of 13 micronutrients analysed, inadequate calcium, vitamin A, riboflavin, folate, and zinc appear to be the most prevalent in 2050. Further, estimates are sensitive to socio-economic growth, which have stronger effects on households' food availability than changes in production driven by alternative greenhouse gas concentrations. As the composition of micronutrient availability by crop varies by country, the characteristics of specific food projections need to be considered when recommending interventions in the food system. The method can also be used to assess alternative scenarios of dietary evolution, and whether food system interventions to enhance nutrient density or availability may meaningfully reduce shortfalls in nutrient availability. The analysis is limited to national average food availability, and further disaggregation of household food availability, by geography or income group, allows for more specific identification of MNDs, and for appropriate interventions.